Teaching yourself social theory - Harris, David, 1947- (Sage Publications, 2003)
This text demonstrates how social theory can be made into an intelligible discourse that touches upon key aspects of everyday life. The abstraction and formalism of much contemporary social theory is criticized as unnecessarily 'scholastic' for the beginner.